200-year ice core bromine reconstruction at Dome C (Antarctica): Observational and modelling results - Burgay, François; Fernandez, Rafael Pedro; Segato, Delia; Turetta, Clara; Blaszczak Boxe, Christopher S.; Rhodes, Rachael H.; Scarchilli, Claudio; Ciardini, Virginia; Barbante, Carlo; Saiz López, Alfonso; Spolaor, Andrea (The Cryosphere)
Bromine enrichment (Brenr) has been proposed as an ice core proxy for past sea-ice reconstruction. Understanding the processes that influence bromine preservation in the ice is crucial to achieve a reliable interpretation of ice core signals and to potentially relate them to past sea-ice variability. Here, we present a 210 years bromine record that sheds light on the main processes controlling bromine preservation in the snow and ice at Dome C, East Antarctic plateau. Using observations alongside a modelling approach, we demonstrate that the bromine signal is preserved at Dome C and it is not affected by the strong variations in ultraviolet radiation reaching the Antarctic plateau due to the stratospheric ozone hole. Based on this, we investigate whether the Dome C Brenr record can be used as an effective tracer of past Antarctic sea ice. Due to the limited time window covered by satellite measurements and the low sea-ice variability observed during the last 30 years in East Antarctica, we cannot fully validate Brenr as an effective proxy for past sea-ice reconstructions at Dome C. Fil: Burgay, François. Universita' Ca' Foscari Di Venezia; Italia. Paul Scherrer Institut; Suiza Fil: Fernandez, Rafael Pedro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Mendoza. Instituto Interdisciplinario de Ciencias Básicas. - Universidad Nacional de Cuyo. Instituto Interdisciplinario de Ciencias Básicas; Argentina Fil: Segato, Delia. Consiglio Nazionale delle Ricerche; Italia. Universita' Ca' Foscari Di Venezia; Italia Fil: Turetta, Clara. Consiglio Nazionale delle Ricerche; Italia. Universita' Ca' Foscari Di Venezia; Italia Fil: Blaszczak Boxe, Christopher S. Howard University; Estados Unidos Fil: Rhodes, Rachael H. University of Cambridge; Estados Unidos Fil: Scarchilli, Claudio. Laboratory of Observations And Measures for the Environment and Climate; Italia Fil: Ciardini, Virginia. Laboratory of Observations And Measures for the Environment and Climate; ...